Synthesis, X-ray structure, spectroscopic characterization and nonlinear optical properties of triaqua(1,10-phenanthroline-2,9-dicarboxylato)manganese(II) dihydrate: A combined experimental and theoretical study - Tamer, Omer; Avci, Davut; Atalay, Yusuf; Cosut, Bunyemin; Zorlu, Yunus; Erkovan, Mustafa; Yerli, Yusuf (Elsevier, 2015)
The triaqua(1,10-phenanthroline-2,9-dicarboxylato)manganese(II) dihydrate complex was prepared and its crystal structure was determined by using single crystal X-ray diffraction. Its structure was also characterized by the applying of F1'-IR, Raman and UV-vis spectroscopies. The manganese(II) ion was located to center of distorted pentagonal-bipyramidal geometry. Electron paramagnetic resonance (EPR) measurement was carried out on the Mn(II) complex. In order to support experimental results, density functional theory calculations were performed at HSEH1PBE level and LanL2DZ basis set. Obtained results indicated that theoretical results can replace the experimental ones. The relatively active nu(CO) nu(CC) and nu(CN) stretching vibration peaks appeared in IR and Raman spectra of complex 1 which are indicators of charge transfer within complex 1 suggest that complex 1 is a good candidate for nonlinear optical materials. The HOMO and LUMO energies determined that complex 1 is stable and the charge transfer occurs within complex 1. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: triaqua(1,10-phenanthroline-2,9-dicarboxylato)manganese(II) dihydrate; FT-IR and Raman; EPR; DFT; Nonlinear optic